Exergy analysis of the diesel pre-reforming SOFC-system with anode off-gas recycling in the SchIBZ project. Part II: System exergetic evaluation. (23rd April 2019) - Valadez Huerta, Gerardo; Álvarez Jordán, Johanan; Marquardt, Tobias; Dragon, Michael; Leites, Keno; Kabelac, Stephan
Abstract: In the first part of the study, we present a model of the solid oxide fuel cell (SOFC) system with anode off-gas recirculation (AGR) in the SchIBZ-project. In this last second paper, we conduct an exergy analysis of this real SOFC plant, using validated models for the reformer and the SOFC module from our first study. We find that an optimum recirculation and low O / C -ratios yield a high exergetic efficiency, due to the small exergy losses in the conversion of chemical energy to electrical power in the SOFC-module under these operation conditions. We conduct our simulations based on a real concept and use validated models, so that the exergy analysis given in this work may be a reliable estimate to the real thermodynamic behavior of this SOFC plant. Highlights: The efficiency of the fuel cell system of the well-known SchIBZ project is analysed. An exergy analysis depending on the recirculation rate and O/C-ratio is conducted. The SOFC model is successful validated within the system in part load. The fuel cell characteristics are calculated with the validated model.